Foodgrain production performance in Bihar: A temporal analysis - KUMAR, ABHAY; SINGH, R K P; CHANDRA, N; BHARATI, R C; KUMAR, UJJWAL; MISHRA, J S (The Indian Journal of Agricultural Sciences, 2018)
The paper presents the growth in foodgrain production in different agro-climatic zones of Bihar during the last 30 years (1984 to 2014). There has been growth in production of foodgrains during the period under study, however, maize and wheat recorded the steady growth during the period. Pulses production got setback in all the agro-climatic zones, particularly during 1984-94. Agro-climatic zone II had an edge over other three agro-climatic zones with respect to increase in foodgrain production mainly due to lower foodgrain production during the base year (TE 1984). Foodgrain production got a boost during 2004-14. Instability in production of all foodgrains was high, but higher instability in production was observed in rice and lower in wheat.The instability in foodgrain production was mainly due to frequent floods in north Bihar and droughts in south Bihar. Also, the growth and instability had positive relationship across all the zones. However, the sustainable increase in foodgrain production was made possible due to improved farmers’ access to inputs and technology. All the three critical inputs (irrigation, fertilizers and HYV seeds) played a significant role in increasing foodgrain production in Bihar.